Cytochrome P450 Monooxygenase/Cytochrome P450 Reductase Bi-Enzymatic System Isolated From Ilex asprella for Regio-Specific Oxidation of Pentacyclic Triterpenoids - Li, Le; Lin, Shumin; Chen, Yuanyuan; Wang, Yaqin; Xiao, Luhua; Ye, Xiaofang; Sun, Lei; Zhan, Ruoting; Xu, Hui (Frontiers in Plant Science, 2022)
Ilex asprella is a plant from Aquifoliaceae. Its root is commonly used as folk medicinal materials in southern China. The chemical compositions of I. asprella are rich in pentacyclic triterpenoids, which show various biological activities and demonstrate a good prospect for drug development. The elucidation of biosynthesis mechanism of triterpenoids in I. asprella could lay important foundations for the production of these precious plant secondary metabolites by metabolic engineering. Our previous studies have revealed IaAO1 (a CYP716A210 homolog) responsible for the C-28 oxidation of α- and β-amyrin. Herein, we reported the identification of three more cytochrome P450 monooxygenase genes IaAO2 (a CYP716A212 homolog), IaAO4 (CYP714E88), IaAO5 (CYP93A220), and a cytochrome P450 reductase gene IaCPR by using Saccharomyces cerevisiae eukaryotic expression system and gas chromatography-mass spectrometry. Among them, the protein encoded by IaAO2 can catalyze the C-28 oxidation of α-amyrin and β-amyrin, IaAO4 can catalyze the C-23 oxidation of ursolic acid and oleanolic acid, while IaAO5 is responsible for the C-24 oxidation of β-amyrin. By introducing three genes IaAO1, IaAO4 and IaCPR into S. cerevisiae. We constructed an engineered yeast strain that can produce C-23 hydroxyl ursane-type triterpenoid derivatives. This study contributes to a thorough understanding of triterpenoid biosynthesis of medicinal plants and provides important tools for further metabolic engineering.